Dendritic Signaling in Inhibitory Interneurons: Local Tuning via Group I Metabotropic Glutamate Receptors - Camiré, Olivier; Lacaille, Jean-Claude; Topolnik, Lisa (Frontiers in Physiology, 2012)
Communication between neurons is achieved by rapid signal transduction via highly specialized structural elements known as synaptic contacts. In addition, numerous extrasynaptic mechanisms provide a flexible platform for the local regulation of synaptic signals. For example, peri- and extrasynaptic signaling through the group I metabotropic glutamate receptors (mGluRs) can be involved in the highly compartmentalized regulation of dendritic ion conductances, the induction of input-specific synaptic plasticity, and the local release of retrograde messengers. Therefore, extrasynaptic mechanisms appear to play a key role in the local tuning of dendritic computations. Here, we review recent findings on the role of group I mGluRs in the dendritic signaling of inhibitory interneurons. We propose that group I mGluRs provide a dual-mode signaling device that integrates different patterns of neural activity. By implementing distinct forms of intrinsic and synaptic regulation, group I mGluRs may be responsible for the local fine-tuning of dendritic function.